Variation in chemical composition and microbial contamination of Maize (Zea mays, L.) seedlings collected from different locations of Buner, Khyber-Pakhtunkhwa, Pakistan - Usman Usman; Hafeez Ur Rahim; Saleem Ullah; Iftikhar Jan; Sajjad Ahmad (Buletin Agroteknologi, 2020)
The current study was aimed to investigate the proximate composition, mineral profile, total bacterial count (TBC), and total fungal count (TFC) in the maize seedlings of “Azam variety” collected from 14 different locations of “District Buner” namely: Agarai, Ambela, Bashkata, Dagger, Elai, Jangai, Karapa, Khanano Derai, Koga, Makhrani, Nawagi, Pir-Baba, Shalbandai, and Sultanwas. The laboratory analysis of maize seedlings revealed that the highest moisture content (13.16 %) was recorded in the samples from Sultanwas, crude fiber (2.55 %) and crude protein (12.38 %) were recorded in Agarai, while ash (3.48 %), crude fat (3.46 %), and NFE (79.94 %) were found maximum in Koga. The lowest value of the moisture (7.66 %) was found in the sample of Shalbandi, crude fiber (0.68 %) was found in Bashkata, NFE (67.28 %) was found in Khanano Derai, whereas ash (1.30 %), crude fat (1.36 %), and crude protein (7.25 %) were reported in Makhrani. In the case of mineral, the maximum Na (71.55 mg 100 g-1), K (415.67 mg 100 g-1), and P (405.41 mg Kg-1) were found in Shalbandai, Daggar, and Sultanwas while the lowest was observed in Elai and Makhrani. Likewise, maximum Fe (6.85 mg 100 g-1) was recorded in Koga, Zn (5.48 mg 100 g-1), and Mn (2.9 mg 100 g-1) in Makhrani, while Cu (2.96 mg 100 g-1) and Mg (175.4 mg 100 g-1) were found in Dagger. However, the minimum concentration of Zn (4.08 mg 100 g-1) and Cu (0.05 mg 100 g-1) were found in Agarai, Mn (0.4 mg 100 g-1) in Sultanwas, Fe (0.45 mg 100 g-1) in Pir-Baba and Mg (111.1 mg 100 g-1) in Jangai. The TBC and TFC were highest in Elai (3.94 ×104) and Pir-Baba (4.46×103) samples while the lowest value was observed in Karapa (3.6×103) and Makhrani (1.3×102), respectively. Besides, some fungal genera were also identified in the collected samples including Aspergillus spp., Fusarium spp., Pencillium spp., and Rhizopus spp. Overall, It was concluded that geographical and environmental conditions are the major contributing factor that impacts the chemical composition and micro-flora of maize variety in different locations.